PENDIDIKAN KRISTEN SEBAGAI FONDASI PEMBENTUKAN KARAKTER PESERTA DIDIK DI ERA DIGITAL - Olivia Massang; Julnita Datu Langi’; Yunike Limbong; Melya Malimbu; Semar Wilkia Palimbunga' (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The development of digital technology has brought significant changes in the mindset, behavior, and character of the younger generation, requiring Christian education to respond adaptively and relevantly. This article examines the role of Christian education as a foundation for character formation in students in the digital era by instilling faith values ​​rooted in Christian teachings. The discussion includes the role of Christian Religious Education teachers as digital role models, the integration of technology into values-based learning processes, and the challenges faced by Christian education in confronting a digital culture that is individualistic, instant, and not always in line with the morality of faith. The research method used is descriptive qualitative through interviews, observations, and documentation studies of teachers, students, and Christian schools. The results of the analysis indicate that Christian education has great potential in shaping students' digital character if faith values ​​are consistently integrated with the wise use of technology.